Total Intravenous Anesthesia versus Inhalation Anesthesia for Breast Cancer Surgery: A Retrospective Cohort Study. (January 2019) - Yoo, Seokha; Lee, Han-Byoel; Han, Wonshik; Noh, Dong-Young; Park, Sun-Kyung; Kim, Won Ho; Kim, Jin-Tae
Editor's Perspective: What We Know about This Topic: IV anesthesia may impair anticancer immunity less than volatile anesthesia and therefore reduce recurrence risk What This Article Tells Us That Is New: In a large propensity-matched retrospective cohort analysis, the authors compared total IV and volatile anesthesia for breast cancer surgery Recurrence hazard was similar with each approach Selection of IV or volatile anesthesia should be based on factors other than cancer recurrence Background: The association between type of anesthesia used and recurrence of cancer remains controversial. This retrospective cohort study compared the influence of total IV anesthesia and inhalation anesthesia on the primary outcome of recurrence-free survival after breast cancer surgery. Methods: The authors reviewed the electronic medical records of patients who had breast cancer surgery at a tertiary care teaching hospital between January 2005 and December 2013. The patients were grouped according to whether IV or inhalation anesthesia was used for surgery. Propensity score matching was used to account for differences in baseline characteristics. Kaplan–Meier survival curves were constructed to evaluate the influence of type of anesthesia on recurrence-free survival and overall survival. The risks of cancer recurrence and all-cause mortality were compared between each type of anesthesia. Results: Of 7, 678 patients who had breast cancer surgery during the study period, data for 5, 331 patients were available for analysis (IV group, n = 3, 085; inhalation group, n = 2, 246). After propensity score matching, 1, 766 patients remained in each group. Kaplan–Meier survival curves showed that there was no significant difference in recurrence-free survival or overall survival between the two groups, with 5-yr recurrence-free survival rates of 93.2% (95% CI, 91.9 to 94.5) in the IV group and 93.8% (95% CI, 92.6 to 95.1) in the inhalation group. Inhalation anesthesia had no significant impact on recurrence-free survival (hazard ratio, 0.96; 95% CI, 0.69 to 1.32; P = 0.782) or overall survival (hazard ratio, 0.96; 95% CI, 0.69 to 1.33, P = 0.805) when compared with total IV anesthesia. Conclusions: The authors found no association between type of anesthesia used and the long-term prognosis of breast cancer. The results of this retrospective cohort study do not suggest specific selection of IV or inhalation anesthesia for breast cancer surgery. Abstract : In a large propensity-matched retrospective cohort analysis, the authors compared total IV and volatile anesthesia for breast cancer surgery. Recurrence hazard was similar with each approach. Selection of IV or volatile anesthesia should be based on factors other than cancer recurrence.Supplemental Digital Content is available in the text.